1935-LB: Integrated Model of Digital Health and Clinic Care Pathway—A Prospective Observational Study to Manage HbA1c Levels and Time in Range among Indian Type 2 Diabetes Mellitus - JOSHI, ARATI K.; SABOO, BANSHI D.; SINGHAL, TAVISHI; CHAKRABARTY, SUJIT; GATTANI, MANSI; NERKAR, PRAJWAL; BANERJEE, TRIJA; GODSE, ANAND S. (Diabetes (New York, N.Y.), 2024)
Aim: To assess the impact of Smit.fit’s CGM-powered Diabetes Care program on reducing HbA1c levels and increasing Time in Range (TIR) for T2DM patients at health clinics. Method: A single group design study of repeated measures evaluated Smit.fit’s 4-month Diabetes Care program deployed at partner health clinics across 50 cities in India. The intervention included glucose monitoring by CGM and HbA1c tests with data-driven behavioural changes facilitated by Smit.fit’s certified health experts tracked on Smit.fit’s app. Results: Of 808 adults, at baseline, 35.1% had severely uncontrolled T2DM (A1c > 9%), 41.5% had uncontrolled T2DM (7% < A1c ≤ 9%) and 23.4% had controlled T2DM (A1c ≤ 7%). The mean age of subjects was 52.34 ± 11.99 yrs, BMI 26.53 ± 4.68, and duration of DM 7.99 ± 7.53 yrs. With Smit.fit’s integrated intervention, a significant difference was observed from baseline HbA1c (8.62 ± 1.95%) to post-program (7.55 ± 1.51%)(p<0.001), CGM Est. A1c (week 1: 8.12 ± 2.54%, week 2: 7.47 ± 2.24%)(p<0.001), and TIR (week 1: 40.32 ± 30.95%, week 2: 47.48 ± 30.79%)(p<0.001). In baseline and Est. A1c, reductions of 1.07, 0.65 respectively, and a 7.16 increase in TIR were observed. Baselining HbA1c levels and HbA1c impact showed a significant positive correlation (r=0.647, p<0.001). In participants with severely uncontrolled T2DM (A1c > 9%), HbA1c reduction of 2.18 ± 1.72% was seen with 72.2% users showing more than 1.0% HbA1c reduction and 19.7% users showing 0.1-1.0% HbA1c reduction. Additional factors like duration of DM, complications and comorbidities lacked significant correlation with HbA1c impact. Conclusion: Smit.fit’s comprehensive approach of data-driven monitoring and coaching led to significant reductions in HbA1c levels and improved glucose control, especially with uncontrolled baseline HbA1c (A1c>7%) where 71.92% users showed >0.5% HbA1c reductions.